Dilemmas and solutions for Chinese lawyers in defending internet financial crime - Xinxin, Mao; Ambaras Khan, Hanna; Ab Rahman, Suhaimi (Human Resource Management Academic Research Society, 2024)
Conventional financial services and the Internet are increasingly intertwined, and Internet financial markets are emerging, resulting in an escalation in both the occurrence and diversity of Internet financial crime. Internet financial crime poses a significant challenge to lawyers in China. This paper aims to study the challenges faced by lawyers in dealing with Internet financial crime in China. Thereafter, this paper suggests making the specialised legislation to better address Internet financial crime. This paper adopts qualitative methodologies, such as desk research and in-depth interviews, in which the respondents are 5 lawyers. The findings indicate that lawyers in China face challenges with Internet financial crime, including the insufficiency of existing related legislation, challenges in prosecution, and the necessity to make the Internet Financial Crime Law of the People's Republic of China.